4.0k views
0 votes
Let f(x) = 3x2 + 2x – 1 and g(x) = x2 – 3x + 1
Find f(x) - g(x)

2 Answers

5 votes
1. subtract like terms
3x^2 - x^2 = 2x^2
2x - -3x = 5x
-1 - 1 = -2
2. combine final product

f(x) - g(x) = 2x^2 + 5x - 2
User Spencer Hill
by
6.1k points
5 votes

Answer:


\boxed {\boxed {\sf f(x)-g(x) = 2x^2 +5x-2}}

Explanation:

We are asked to find f(x) - g(x) or the difference between the two functions. We know that the functions are:

  • f(x)= 3x² +2x -1
  • g(x)= x² - 3x +1

We can substitute the expressions for the functions.


f(x) - g(x)


(3x^2 +2x-1)- (x^2-3x+1)

First, we must distribute the -1 in front of the second set of parentheses. Multiply each term inside the parentheses by -1.


(3x^2+2x-1) + ( -1*x^2) + (-1* -3x) + (-1*1)


(3x^2+2x-1) + (-x^2)+ (3x) + (-1)


(3x^2+2x-1)+ (-x^2+3x-1)

Now we can combine like terms. The terms with x² can be combined, then the terms with x, and finally the constants (terms without variables).


(3x^2+ -x^2 ) + (2x+3x) + (-1+ -1)


(2x^2) + (5x) + (-2)

Eliminate any unnecessary addition signs and parentheses.


2x^2+5x-2

User Cordel
by
6.4k points